Literature Sibling Relationships dalam Keluarga dengan Anak Autism Spectrum Disorded - Safana Azzahra Putri Adika; Stephani Raihana Hamdan (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Siblings play a vital role in the family system throughout life, including within families of children with Autism Spectrum Disorder (ASD). This study aims to examine the quality of sibling relationships in families raising children with ASD through a literature review approach. The findings indicate that the limitations experienced by children with ASD, particularly in communication and behavior, often create challenges for their typically developing siblings, such as emotional stress, difficulties in social interaction, feelings of embarrassment in public settings, and an overwhelming sense of responsibility. Nevertheless, many siblings also demonstrate strong expressions of affection, empathy, and acceptance toward their sibling with ASD. These findings highlight the importance of the family and broader social environment in providing adequate social support. Thus, understanding siblings’ experiences is expected to foster the development of more harmonious and supportive family relationships. Abstrak. Siblings merupakan bagian penting dalam sistem keluarga yang memiliki peran sepanjang hidup, termasuk dalam keluarga dengan anak penyandang Autism Spectrum Disorder (ASD). Penelitian ini bertujuan untuk mengkaji kualitas sibling relationships dalam keluarga dengan anak ASD melalui pendekatan studi literatur. Hasil tinjauan menunjukkan bahwa keterbatasan anak dengan ASD dalam aspek komunikasi dan perilaku seringkali menimbulkan tantangan bagi saudara kandung mereka, seperti stres emosional, kesulitan dalam menjalin interaksi sosial, perasaan malu di lingkungan sosial, hingga munculnya tanggung jawab yang berlebihan. Meski demikian, mereka juga menunjukkan bentuk kasih sayang, empati, dan penerimaan yang kuat. Temuan ini menekankan pentingnya peran keluarga dan lingkungan dalam menyediakan dukungan sosial. Dengan demikian, pengalaman siblings diharapkan dapat mendorong terciptanya hubungan keluarga yang lebih harmonis dan suportif.